NATURE AS WITNESS: SYMBOLISM AND DISPLACEMENT IN MANJUSHREE THAPA’S SEASONS OF FLIGHT - RAMESH PRASAD ADHIKARY (Tạp chí Khoa học xã hội Thành phố Hồ Chí Minh, 2025)
Manjushree Thapa’s Seasons of Flight (2010) intricately weaves the natural world into its narrative to explore themes of displacement, identity, and resilience through the journey of Prema, a Nepali woman navigating migration to the United States. This study examines the novel’s symbolic use of nature, addressing a critical gap in existing scholarship, which has predominantly focused on socio-political and cultural dimensions while overlooking ecological and symbolic nuances. Employing qualitative literary analysis through ecocritical and postcolonial theoretical frameworks, the research reveals how Thapa’s vivid natural imagery – contrasting Nepal’s lush landscapes with California’s aridity – mirrors Prema’s emotional states, serving as a dynamic metaphor for her psychological transformation. The analysis demonstrates that nature functions as a site of cultural memory and resistance, anchoring Prema’s identity amid dislocation, while resilient elements like desert flora symbolize her adaptation. Furthermore, the novel critiques environmental exploitation in industrialized settings, contrasting it with Nepal’s harmonious human – nature relationships, aligning with ecocritical concerns about globalization. The recurring motif of avian migration underscores the duality of flight as both liberation and loss, encapsulating the diasporic experience’s complexities. By situating the narrative within ecocritical and postcolonial discourse, this study highlights Thapa’s literary innovation in merging ecological and cultural critiques, offering fresh insights into how natural symbolism articulates inner turmoil and resilience in migrant narratives. The findings underscore the importance of integrating ecological perspectives into postcolonial literary studies, enriching understandings of identity, belonging, and environmental interconnectedness in an increasingly globalized world. This research contributes to broader conversations in ecocriticism and diaspora studies, affirming literature’s role in reflecting the entangled realities of human and environmental displacement.